2018
DOI: 10.1007/s12035-018-1131-8
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Periaqueductal Gray Matter in Lower Urinary Tract Function

Abstract: The periaqueductal gray matter (PAG), as one of the mostly preserved evolutionary components of the brain, is an axial structure modulating various important functions of the organism, including autonomic, behavioral, pain, and micturition control. It has a critical role in urinary bladder physiology, with respect to storage and voiding of urine. The PAG has a columnar composition and has extensive connections with its cranially and caudally located components of the central nervous system (CNS). The PAG serve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 140 publications
(193 reference statements)
0
36
0
Order By: Relevance
“…In addition, optogenetic studies revealed that vlPAG GABAergic neurons regulated non-REM and REM sleep (Weber et al, 2018). Other studies based on genetically engineered systems showed that activation of vlPAG GABAergic neurons delayed detrusor contraction and inhibited voiding (Zare et al, 2018). In contrast, PPT GABAergic neurons are mostly involved in gait and balance regulation, a function that is not identified in LPT GABAergic neurons.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, optogenetic studies revealed that vlPAG GABAergic neurons regulated non-REM and REM sleep (Weber et al, 2018). Other studies based on genetically engineered systems showed that activation of vlPAG GABAergic neurons delayed detrusor contraction and inhibited voiding (Zare et al, 2018). In contrast, PPT GABAergic neurons are mostly involved in gait and balance regulation, a function that is not identified in LPT GABAergic neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Although not a watershed area, the PAG is a highly active metabolic brain region that may have suffered from the insult of low circulating oxygen levels in our patient. While best known for the inhibition of pain, the PAG has been implicated in micturition control, migraines, vertical ophthalmoplegia, and, in this case, our patient presenting with esotropia [7].…”
Section: Discussionmentioning
confidence: 99%
“…Step 2C: If periaqueductal grey damaged patient likely to have stress incontinence [8]. Initiate psychology consult.…”
Section: Section 2: Clinical Management Strategy By Injury Typementioning
confidence: 99%